(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the methods for evaluating the effectiveness of protected natural areas in nature conservation. To ensure the effectiveness of the territorial system of nature protection, it is necessary to conduct comprehensive research on the current state of the existing system of protected natural areas. In assessing the degree of landscape diversity within the system of protected natural areas, we utilize the Landscape Representativeness Index (LRI). This approach takes into account indicators such as the ecological status of landscapes, their share in the total area of the region, their proportion within the system of protected natural areas, the level of uniqueness, and the recommended minimum share for the establishment of protected natural areas. Such assessments are crucial for creating a regional level of representativeness within the system of protected natural areas.